Learning shapes and colors using JomLearn & Play Application for children / Madiawati Musa … [et al.] - Musa, Madiawati; Mazlan, Azlimi; Engku Mohamed Fathilullah, Engku Nuraisha; Amir, Aimi Liyana; Zulkifli, Norlindamalia; Mohd Salleh, Nurhashikin (Faculty of Computer and Mathematical Sciences, 2020)
Learning shapes and colors are the basic cognitive development for children. Children learn best through sorting size, shapes, and colors. Nowadays, most of the applications available are using English language. This study found that there are very limited applications using Malay language. The current existing applications are available in Indonesia language. “JomLearn & Play” is the application focus on children to learn the basic shapes and colors using Malay language. The method used is ADDIE model consists of analysis, design, development, implementation, and evaluation. The “JomLearn & Play” application can help for children in early stage to learn about shapes and colors.